Solomon Dersso, Forty years of the African Charter and the reform issues facing the discourse and practice of human rights (Czterdzieści lat Karty Afrykańskiej i problemy reform, przed którymi stoi polemika z prawami człowieka i praktyka ich stosowania) „African Human Rights Law Journal” 2021, vol. 21, no. 2 - Dąbrowska, Anna (Studia Prawa Publicznego, 2022)
Solomon Dersso, Forty years of the African Charter and the reform issues facing the discourse and practice of human rights (Czterdzieści lat Karty Afrykańskiej i problemy reform, przed którymi stoi polemika z prawami człowieka i praktyka ich stosowania) „African Human Rights Law Journal” 2021, vol. 21, no. 2, s. 649–668, http://dx.doi.org/10.17159/1996-2096/2021/v21n2a26